2020
DOI: 10.1177/0024363920920400
|View full text |Cite
|
Sign up to set email alerts
|

The Spiritual Works of Mercy as a Tool to Prevent Burnout in Medical Trainees

Abstract: Burnout is highly prevalent among physicians and is associated with negative patient outcomes. Furthermore, medical training is a particularly vulnerable time as studies show that medical students, residents, and fellows experience burnout and emotional exhaustion at higher rates than both the general population and physicians in practice. Multiple recent studies have demonstrated the practice of religion and spirituality to be protective against burnout in trainees. Can Catholic academic physicians transfer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The habit of praying every day was a significant protective factor for burnout, and this may occur through the perception of divine protection, as mentioned by Tavares Quelho, while discussing spirituality as a dimension of protection and humanization, in addition to bringing the character of hope ( Tavares, 2020 ). A different study with healthcare professionals in Hong Kong demonstrated in a regression analysis that daily spiritual practice acts as a protective factor not only against burnout, but also against depression and anxiety ( Shaniuk, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The habit of praying every day was a significant protective factor for burnout, and this may occur through the perception of divine protection, as mentioned by Tavares Quelho, while discussing spirituality as a dimension of protection and humanization, in addition to bringing the character of hope ( Tavares, 2020 ). A different study with healthcare professionals in Hong Kong demonstrated in a regression analysis that daily spiritual practice acts as a protective factor not only against burnout, but also against depression and anxiety ( Shaniuk, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It’s a rare month that I don’t have an “old-timer” physician regale me with a story of a diagnosis missed or delayed because of the reliance on tests and the failure to do a physical exam; these experiences are now making their way to the medical literature, online and otherwise (Boodman 2014). As it is with the rest of the world, depression, anxiety, burnout, and suicide are significant problems among physicians and are on the rise (Shaniuk 2020).…”
mentioning
confidence: 99%
“…The last six months have seen multiple curricular proposals for wellness and resilience building [14][15][16][17][18][19]. In an assessment of integrative resilience tips to embrace during public health crises (eg.…”
mentioning
confidence: 99%
“…The topic areas include: a holistic view, a calm mind, general awareness, relationships, healthy habits, reflective writing, appreciative inquiry, moral resilience, certain academic considerations, an optimization of system culture, trauma-informed care, and the encouragement of the act of seeking help if needed [14]. In another approach, Shaniuk (2020) draws a reference to The Seven Spiritual Works of Mercy (counsel the doubtful, instruct the ignorant, admonish the sinner, comfort the sorrowful, forgive injuries, bear wrongs patiently, and pray for the living and the dead) as a foundation for teaching physicians to uplift students during this particularly trying time [19].…”
mentioning
confidence: 99%